Simplified equations to represent irregular flow in open channels using numerical methods - Jalil, Shakir Eabdallatif (Al-Mukhtar Journal of Sciences, 1996)
The research deals with the irregular flow in exposed channels using Runge-Kutta numerical method in solving the basic differential equation for flow. Then the research deduces simplified unitless equations from the results of solving the differential equation using the computer, as these equations help to design and study the flows in the channels of regular section without returning to the integration of the general differential equation.